PERAN DAN TANTANGAN GENERASI Z SEBAGAI TENAGA PENDIDIK DALAM MENGHADAPI ERA DIGITAL - Ihtiar Akbar, Hasan; Hapipi, Hapipi; Mustari, Mohammad (Berajah Journal, 2024)
The rapid development of information and communication technology has brought significant changes to various aspects of life, including education. The digital era presents not only new opportunities but also complex challenges for educators, particularly for Generation Z. This research aims to explore the roles and challenges faced by Generation Z as educators in the digital age. The method used in this study is descriptive qualitative, specifically library research. The findings indicate that in the digital era, Generation Z plays a crucial role as educators by leveraging their familiarity with technology to create interactive and relevant learning experiences. They encourage collaboration among students through projects and game elements, as well as linking the material to current issues. However, the challenges they face include a lack of experience in classroom management, difficulties in balancing teaching tasks with administrative duties, and high expectations from parents and schools. To address these challenges, Generation Z utilizes personal experiences and self-directed learning while collaborating with fellow educators. Enhanced training in technology and classroom management is essential to support their effectiveness in fulfilling their roles as educators.